A Critical Assessment of the Enforcement Regime for Combatting Money Laundering in Nigeria. Issue 1 (February 2020) - Ojukwu-Ogba, Nelson E.; Osode, Patrick C.
Abstract : The menace of corruption in public sector governance has remained an intractable challenge in most African countries. Since the reintroduction of civilian democracy in 1999 in Nigeria, the state has strived to entrench openness and transparency, which are indispensable to the attainment of rapid socio-economic development. The government has pursued the policy of eliminating corruption in the public and private sectors through the enactment or review of statutes aimed at the prevention of financial crimes, especially money laundering. This article assesses the effectiveness of the statutory instruments in realising the desired objectives of curbing money laundering and institutionalising transparency in Nigeria.